Peningkatan Kemampuan Membuat Soal HOTS bagi Guru Matematika dan Sains se-Indonesia - Ni Made Intan Kertiyani; Churun Lu'Luil Maknun; Rahma Nasir; Uncok Manigor Jokkas Siahaan; Manto Lumban Gaol (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
Higher Order Thinking Skills (HOTS) is one of the goals to be achieved in the 2013 curriculum. One of the tools to measure students' ability in this skills is through HOTS questions. Based on the questionnaire given to mathematics and science teachers throughout Indonesia, the teachers felt the need to give HOTS questions in class and were interested in attending seminars related to this. Based on the results of the questionnaire, a community service program was to improve the ability of Mathematics and Science teachers in Indonesia to make HOTS questions. The purpose of this webinar is to provide intensive information on the design of HOTS-based learning, provide detailed examples of HOTS-based learning and tips for creating or selecting HOTS-based questions that are relevant to students and scientific developments. This activity was carried out virtually by involving 42 mathematics and science teachers in Indonesia. The evaluation data filled in by the participants at the end of the event showed that the activity was going well. Participants agreed that the material presented answered the participants' needs. Participants also felt an increase in their ability to make HOTS questions after attending this webinar.